Isoniazid Poisoning: A Pediatric Simulation Case for Emergency Medicine Residents - Cynthia Santos; Adam Pomerleau; Stephen Alerhand; Jeffrey N. Siegelman (Association of American Medical Colleges, 2016)
Abstract Introduction Seizures in the setting of isoniazid (abbreviated INH, from isonocotinylhydrazide) toxicity can be intractable and persistent despite treatment with the usual status epilepticus (SE) medications. If not recognized in a timely fashion, SE can lead to significant morbidity and mortality. This simulation scenario instructs emergency medicine and pediatric residents and fellows in any year of training on the principles and management strategies of approaching a pediatric patient with SE due to INH toxicity. Methods This scenario presents a 5-year-old pediatric patient brought into the emergency department after a witnessed seizure at home, another en route to the emergency department, and a third event in front of the medical provider. This scenario was designed to include one 15- to 20-minute group simulation session, followed by a 10- to 15-minute debriefing of the case. The simulation can be run with a minimum of two participants-one to play the role of physician and the other to play the case director or simulation operator. Also included are visual stimuli consisting of relevant lab results, imaging, and other diagnostic studies. Finally, an educational handout created for all simulation participants reviews important teaching points related to the case. Results To date, 30 residents have participated in this simulation during one of the weekly conference days. In the postactivity survey reviews, residents have reaffirmed their appreciation for their simulation time and have requested more exposure. Discussion Simulation scenarios are an ideal teaching tool for rare and life-threatening diseases, as medical trainees will have little to no prior applied experience with such conditions.